Survey data on cost and benefits of climate smart agricultural technologies in western Kenya - Karanja Ng'ang'a, Stanley; Mwungu, Chris Miyinzi; Mwongera, Caroline; Kinyua, Ivy Wambui; Notenbaert, An Maria Omer; Girvetz, Evan Hartunian (Elsevier, 2018)
This paper describes data that were collected in three counties of western Kenya, namely Siaya, Bungoma, and Kakamega. The main aim of collecting the data was to assess the climate smartness, profitability and returns of soil protection and rehabilitation measures. The data were collected from 88 households. The households were selected using simple random sampling technique from a primary sampling frame of 180 farm households provided by the ministry of agriculture through the counties agricultural officers. The surveys were administered by trained research assistants using a structured questionnaire that was designed in Census and Survey Processing System (CSPro). Later, the data was exported to STATA version 14.1 for cleaning and management purposes. The data are hosted in an open source dataverse to allow other researchers generate new insights from the data (http://dx.doi.org/10.7910/DVN/K6JQXC).